دورالحملات الاعلامية بمديرية الصناعة التقليدية و الحرفية في نشرالحرف التقليدية في نشر الحرف التقليدية بين الشباب - زنبط حسين; شقنان بلعباس; د/ سميرة مراح (جامعة عمار ثليجي الاغواط, 2024)
ملخص: تبحث هذه الدراسة في دور الحملات الإعلامية في نشر الصناعات التقليدية بين الشباب في ولاية الأغواط بالجزائر. كشفت الدراسة الميدانية عن وعي عميق لدى الحرفيين بأهمية صناعاتهم ودورها في الحفاظ على التراث الثقافي و الهوية الوطنية، كما أبرزت ثقتهم بقدرة الإعلام على تعزيز هذه الصناعات. و بالرغم من التأثير الإيجابي للحملات الإعلامية في الترويج للصناعات التقليدية، إلا أنها تعاني من قصور في توفير معلومات كافية عن فرص العمل و التحديات التي قد تواجه الشباب. و خلصت الدراسة إلى ضرورة تحسين جودة الحملات الإعلامية لتصبح أكثر شمولية و تفاعلية لتلبية حاجات الشباب وتشجيعهم على امتهان الحرف التقليدية. الكلمات المفتاحية: الحملات الإعلامية، الصناعات التقليدية، الشباب الجزائري، التراث الثقافي. Abstract This study explores the role of media campaigns in promoting traditional industries among the youth in the wilaya of Laghouat, Algeria. The field study revealed a deep awareness among craftsmen of the importance of their industries and their role in preserving cultural heritage and national identity, as well as their confidence in the media's ability to enhance these industries. Despite the positive impact of media campaigns in promoting traditional industries, they suffer from a lack of sufficient information about job opportunities and challenges that young people may face. The study concluded that it is necessary to improve the quality of media campaigns to make them more comprehensive and interactive in order to meet the needs of young people and encourage them to practice traditional crafts. Keywords: Media campaigns, traditional industries, youth, Algeria, Laghouat, national identity, job opportunities, cultural heritage.